2009
DOI: 10.1080/02705060.2009.9664317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Traps Used for Capturing Wild Crayfish

Abstract: We compared two passive wire traps for trapping wild crayfish-a trap designed specifically for capturing crayfish and a minnow trap commonly adapted for this purpose. We investigated crayfish capture efficiency, retention of captured crayfish, and capture of non-target finfishes for both trap types in mesocosm and field experiments. The crayfish traps captured more crayfish than the minnow traps in both settings. The minnow traps better retained captured crayfish; however, they also captured significantly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…We chose the number of traps and trap replicates based on a preliminary power analysis that suggested that increasing the number of observations (e.g., by increasing the number of overall traps) would improve our ability to detect the effect of trap deployment time on crayfish catch. To address the potential effect of trap density on crayfish catch, we placed traps 1 to 3 m from other traps (Mangan et al 2009, Peay et al 2009, Green et al 2018. Traps with 1-d deployments were redeployed after checking each day; traps with 2-d deployments were checked after 2 d and redeployed 1 additional time in a given trapping week; and traps with 4-and 7-d deployments were only checked once in a given trapping week.…”
Section: Trap Design Placement and Sampling Schemamentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the number of traps and trap replicates based on a preliminary power analysis that suggested that increasing the number of observations (e.g., by increasing the number of overall traps) would improve our ability to detect the effect of trap deployment time on crayfish catch. To address the potential effect of trap density on crayfish catch, we placed traps 1 to 3 m from other traps (Mangan et al 2009, Peay et al 2009, Green et al 2018. Traps with 1-d deployments were redeployed after checking each day; traps with 2-d deployments were checked after 2 d and redeployed 1 additional time in a given trapping week; and traps with 4-and 7-d deployments were only checked once in a given trapping week.…”
Section: Trap Design Placement and Sampling Schemamentioning
confidence: 99%
“…In addition to sampling bias, traditional passive baited minnow traps can be a troublesome tool for researchers and managers because of their inability to discriminate between target and non-target species. Bycatch of non-target organisms can be an unintended consequence of any manual trapping program, such as reported by Mangan et al (2009) and Swartz and Miller (2018). Although one could take a conservation-management perspective to rationalize that the long-term benefit of invasive crayfish removal justifies the temporary impact on non-target taxa, removal projects should aim to maximize crayfish removal while minimizing or eliminating non-target bycatch.…”
mentioning
confidence: 99%